2022
DOI: 10.1128/jcm.02374-21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 Variants on the Analytical Sensitivity of rRT-PCR Assays

Abstract: Emerging severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants with enhanced transmissibility, pathogenicity, and immune escape ability have ravaged many countries and regions, which has brought substantial challenges to pandemic prevention and control. Real-time reverse transcriptase PCR (rRT-PCR) is widely used for SARS-CoV-2 detection but may be limited by the continuous evolution of the virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Once the mutations of the virus are located at the primer/probe-targeted regions, the effectiveness of molecular assays might be influenced to some degree. In this study, in contrast to the WT strain, impaired analytical sensitivity was found in the Delta variant using Kit N04, both for the single sampling tests (19/27 versus 11/27, P = 0.028) and for the 20-in-1 pooling tests (16/27 versus 7/27, P = 0.013), whereas the Omicron variant had no significant effect on the 5 rRT-PCR kits and the POCT kit, which is in concordance with the findings of a prior study ( 45 ). However, the 19 rapid antigen tests showed an insignificant difference in analytical sensitivity for the 3 inactivated cell culture supernatants and the 5 recombinant N proteins, which might be attributable to the fact that nearly all of the rapid antigen tests target the SARS-CoV-2 nucleocapsid protein, which has less of a probability to mutate ( 12 ).…”
Section: Discussionsupporting
confidence: 90%
“…Once the mutations of the virus are located at the primer/probe-targeted regions, the effectiveness of molecular assays might be influenced to some degree. In this study, in contrast to the WT strain, impaired analytical sensitivity was found in the Delta variant using Kit N04, both for the single sampling tests (19/27 versus 11/27, P = 0.028) and for the 20-in-1 pooling tests (16/27 versus 7/27, P = 0.013), whereas the Omicron variant had no significant effect on the 5 rRT-PCR kits and the POCT kit, which is in concordance with the findings of a prior study ( 45 ). However, the 19 rapid antigen tests showed an insignificant difference in analytical sensitivity for the 3 inactivated cell culture supernatants and the 5 recombinant N proteins, which might be attributable to the fact that nearly all of the rapid antigen tests target the SARS-CoV-2 nucleocapsid protein, which has less of a probability to mutate ( 12 ).…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, the patient’s samples gave positive results for E and RNA-dependent RNA polymerase (RdRP)/S genes, mirroring the scenario with SARS-CoV-2 Omicron variant-infected patients presented here. Concomitantly, Chen et al ( 17 ) assessed the impact of six important SARS-CoV-2 variants (Alpha, Beta, Gamma, Delta, Omicron, and Fin-796H) on the analytical sensitivity of the five commercial SARS-CoV-2 PCR assays most used in Chinese laboratories. The authors ( 17 ) found that Alpha and Omicron variants had no significant effect on the assays’ detection capability, whereas remarkably, one of these assays failed to detect the N gene in the Fin-796H variant.…”
Section: Observationmentioning
confidence: 99%
“…Concomitantly, Chen et al ( 17 ) assessed the impact of six important SARS-CoV-2 variants (Alpha, Beta, Gamma, Delta, Omicron, and Fin-796H) on the analytical sensitivity of the five commercial SARS-CoV-2 PCR assays most used in Chinese laboratories. The authors ( 17 ) found that Alpha and Omicron variants had no significant effect on the assays’ detection capability, whereas remarkably, one of these assays failed to detect the N gene in the Fin-796H variant. Not surprisingly, Fin-796H (B.1.1.318), which is not a WHO-designated VOC, was known to carry a mutation in the region targeted by China’s CDC-recommended N-gene assay ( 17 ).…”
Section: Observationmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, the mutations could limit the efficacy and sensitivity of the test. In the assay kit of Sansure Biotech (Changsha, China), the gamma variant affected the PCR amplification efficiency of ORF1ab (Chen et al, 2022b). Rajib et al (2022) also reported that the Delta variant containing a mutation in the probe binding region of the E gene exhibited atypical PCR amplification and might induce false negative results.…”
Section: The Influences Of Severe Acute Respiratory Syndrome Coronavi...mentioning
confidence: 99%